Canadian Provincial Party Systems: An Analytical Typology. Issue 2 (3rd April 2021) - Wesley, Jared J.; Buckley, Clare
ABSTRACT: The competitiveness of party politics is often viewed as a barometer of the health of modern democracies. Using the Canadian federation as a laboratory, this article advances a new framework for comparing party systems across space and time. The model incorporates two core dimensions of political party systems: conflict intensity and competitiveness. Conflict intensity—or the degree of adversarialism in the system—encompasses the extent to which parties engage in centripetal or centrifugal modes of competition. Competitiveness measures the uncertainty of typical elections in the system, including the overall balance of popular support among parties and the vulnerability of governments. A concluding discussion establishes the value of this exercise, and suggests ways in which elements of this framework may be used as independent and dependent variables in future inquiries about Canadian provincial politics and other party systems.